2015
DOI: 10.1111/jvim.13661
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Intrinsic Rhythm Evaluation in Dogs with Atrioventricular Block

Abstract: BackgroundAtrioventricular block (AVB) is a conduction abnormality along the atrioventricular node that, depending on etiology, may lead to different outcomes.ObjectivesTo evaluate variations of intrinsic rhythm (IR) in dogs that underwent pacemaker implantation (PMI).AnimalsMedical records of 92 dogs affected by 3rd degree atrioventricular block (3AVB), advanced 2nd degree AVB (2AVB), paroxysmal 3AVB, 2:1 2AVB, or 3AVB with atrial fibrillation (AF) were retrospectively reviewed.MethodThe patient IR was docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…In particular, paroxysmal third-degree AVB progressed to permanent thirddegree AVB and most cases of 2:1 second degree AVB also progressed to third-degree AVB [35]. These findings are not in agreement with human medicine, in which 2:1 second degree AVB is considered to be stable [123], but support the need for PM implantation in dogs affected by paroxysmal third-degree AVB and 2:1 s degree AVB [35].…”
Section: Indications For Pacing and Choice Of Pacing Modementioning
confidence: 88%
See 4 more Smart Citations
“…In particular, paroxysmal third-degree AVB progressed to permanent thirddegree AVB and most cases of 2:1 second degree AVB also progressed to third-degree AVB [35]. These findings are not in agreement with human medicine, in which 2:1 second degree AVB is considered to be stable [123], but support the need for PM implantation in dogs affected by paroxysmal third-degree AVB and 2:1 s degree AVB [35].…”
Section: Indications For Pacing and Choice Of Pacing Modementioning
confidence: 88%
“…In such cases, small, uncontrolled studies have shown an improvement in symptoms with normalization of the PQ interval with dual-chamber pacing (AV resynchronization therapy) [67]. In veterinary medicine, one study that analyzed long-term intrinsic rhythm in dogs with AV nodal conduction disturbances had proven that the majority of cases showed persistent or progressive AVB [35]. In particular, paroxysmal third-degree AVB progressed to permanent thirddegree AVB and most cases of 2:1 second degree AVB also progressed to third-degree AVB [35].…”
Section: Indications For Pacing and Choice Of Pacing Modementioning
confidence: 99%
See 3 more Smart Citations